2015
DOI: 10.1186/s40623-015-0242-y
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetism and U-Pb geochronology of the late Cretaceous Chisulryoung Volcanic Formation, Korea: tectonic evolution of the Korean Peninsula

Abstract: Late Cretaceous Chisulryoung Volcanic Formation (CVF) in southeastern Korea contains four ash-flow ignimbrite units (A1, A2, A3, and A4) and three intervening volcano-sedimentary layers (S1, S2, and S3). Reliable U-Pb ages obtained for zircons from the base and top of the CVF were 72.8 ± 1.7 Ma and 67.7 ± 2.1 Ma, respectively. Paleomagnetic analysis on pyroclastic units yielded mean magnetic directions and virtual geomagnetic poles (VGPs) Our best estimates of the paleopoles for A1, A3, and A4 are in remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Based on a paleomagnetic study on Miocene sediments from the Oidawara Formation, eastern southwest Japan, Hoshi et al (2015) revealed that clockwise rotation of southwest Japan occurred mainly between 17.5 and 15.8 Ma, at a rotation rate of ~23°/Myr. Furthermore, Jeong et al (2015) presented the tectonic evolution of the Korean Peninsula based on the paleomagnetism and U-Pb geochronology of the late Cretaceous Chisulryoung Volcanic Formation. The weighted mean ages obtained by U-Pb zircon dating from the base and top of the formation are 72.8 ± 1.7 and 67.7 ± 2.1 Ma, respectively.…”
Section: Paleomagnetism: Tectonicsmentioning
confidence: 99%
“…Based on a paleomagnetic study on Miocene sediments from the Oidawara Formation, eastern southwest Japan, Hoshi et al (2015) revealed that clockwise rotation of southwest Japan occurred mainly between 17.5 and 15.8 Ma, at a rotation rate of ~23°/Myr. Furthermore, Jeong et al (2015) presented the tectonic evolution of the Korean Peninsula based on the paleomagnetism and U-Pb geochronology of the late Cretaceous Chisulryoung Volcanic Formation. The weighted mean ages obtained by U-Pb zircon dating from the base and top of the formation are 72.8 ± 1.7 and 67.7 ± 2.1 Ma, respectively.…”
Section: Paleomagnetism: Tectonicsmentioning
confidence: 99%
“…A detailed paleomagnetic analysis of the CVF was reported elsewhere (Jeong et al, 2015), hence, only a new rock magnetic investigation is described here. For sample 27A, the alternatingfield (AF) decays of natural remanent magnetization (NRM) were relatively hard, with median destructive field (MDF) of ∼30 mT ( Figure 4A).…”
Section: Rock Magnetic Propertiesmentioning
confidence: 99%
“…Member Description Intrusion Gadaeri granite intrusion K/Ar biotite age: 63.9 ± 1.8 Ma (Reedman et al, 1989) 2nd eruptive cycle A4 Welded lithic-rich tuff U/Pb zircon age: 67.7 ± 2.1 Ma (Jeong et al, 2015) Intrusion Cheokwari granodiorite intrusion K/Ar hornblende age: 76.3 ± 11.7 Ma (Reedman et al, 1989) 1st eruptive cycle S3 Tuffaceous sediments…”
Section: Eventsmentioning
confidence: 99%
See 2 more Smart Citations